Bidirectional variability in motor cortex excitability modulation following 1 mA transcranial direct current stimulation in healthy participants. Issue 15 (5th August 2016) - Strube, Wolfgang; Bunse, Tilmann; Nitsche, Michael A.; Nikolaeva, Alexandra; Palm, Ulrich; Padberg, Frank; Falkai, Peter; Hasan, Alkomiet
Abstract: Due to the high interindividual response variability following transcranial direct current stimulation (tDCS), it is apparent that further research of the long‐lasting effects of the stimulation technique is required. We aimed to investigate interindividual variability following anodal tDCS and cathodal tDCS in a large‐scale prospective cross‐over study. Motor cortex physiology measurements were obtained using transcranial magnetic stimulation (TMS) in 59 healthy participants comparing motor‐evoked potential (MEP) magnitudes following two tDCS paradigms: 1 mA anodal tDCS for 13 min and 1 mA cathodal tDCS for 9 min. Analysis compared MEP changes over time for both polarities. Additionally, we applied hierarchical cluster analysis to assess the dynamics of poststimulation changes. Overall, anodal tDCS resulted in a significant increase in corticospinal excitability lasting for 40 min poststimulation, whereas cathodal tDCS did not alter corticospinal excitability. Cluster analysis revealed for cathodal tDCS both a cluster showing significant stable MEP reduction and a second cluster displaying MEP increase over time. Two diametrical clusters were also found for anodal tDCS. Regardless of polarity, individuals with MEP increase following stimulation showed steeper cortical recruitment curves compared to the clusters with decreased MEP magnitudes. The observed findings confirm a bidirectional modulation of corticospinal excitability following 1 mA tDCS in separate subgroups and the relationship to cortical recruitment. Abstract : 1mA anodal and cathodal transcranial direct current stimulation display a significant inter‐subject variability. Response clusters showing increases or decreases in corticospinal excitability following both anodal and cathodal tDCS can be extracted allowing for a separation of different response patterns. Regardless of polarity, clusters of increased corticospinal excitability following anodal or cathodal tDCS are characterized by steeper cortical recruitment. Our results help to better understand the individual response heterogeneity to standard motor‐cortical transcranial direct current stimulation.